Mercado do Porto do Sal: perspectivas de musealização do espaço por meio da presença de mulheres artistas - COSTA, Paloma Silva da (2019)
Porto do Sal Market - Perspectives of Musealization of Space Through the Presence of Women Artists is a work that aims to analyze this space in function of the sociocultural dynamics that it holds in order to develop perspectives of musealization of this place from the practices and interactions that women artists construct in this landscape, which, in a consequent way, imply on the Porto do Sal Market significations that go beyond their categorization as a commercial space. This study starts from questions that seek to understand the potential of musealization, from the concept of the Territory Museum, that the Porto do Sal market has acquired with these characters - female artists; what are they and in what way do these relations between this patrimony and these people re-signify the meanings that the market has in its sociocultural context in contemporary times? As a theoretical basis I used the studies of Diana Lima (2012), Mario Chagas (2014), Joice Berth (2018), Helena Dodd (1991), Gabriela Figurelli (2011), Veronique Isabelle (2014), Aida Rechena(2014) e Celma Chaves (2013). The methodology is qualitative and unfolds in processes that are linked to bibliographic research and analysis, in document collection and organization of files from the field research and in the conduct of interviews. The relevance of this work focuses on the importance that the Port of Sal Market has in this present time through the presence of these artists who fulfill the role of resonant voices, which evoke the materiality and immateriality that this space possesses from of actions that denote a discourse and practice linked to the forms of feminine resistance in a conflicting space, but which also builds meanings for valuing assets, commitment to the right to citizenship, social dignity and, above all, to the service of the community of people who constitute identities and affective memories intertwined with this edification.